Membrane transport and permeation of drugs - Kumar M.; Jha A.; Mishra B. (My University, 2025)
Most newly developed drugs have limited clinical applications due to unknown and varying transport and permeation across the biological membrane, which in turn influence the drug bioavailability. Therefore, methods for the assessment of drug permeation across biological membrane barriers are a must. Various in vitro and ex vivo methods are available for primary investigation of drug permeation across different biological barriers. The artificial membrane that mimics real biological membranes also gain wide popularity in the investigation of membrane permeation of drugs. This chapter discusses in detail all the aspects of drug permeation including the mechanism and tools utilized to assess the rate and extent of drug permeation through biological barriers, mainly gastric mucosa, intestinal mucosa, blood-brain barrier (BBB), skin, and corneal epithelium. © 2024 Elsevier Inc. All rights are reserved including those for text and data mining AI training and similar technologies.